Embodying Texts and Tradition: Ethnographic Film in a South Indian Advaita Vedānta Gurukulam - Dalal, Neil (Journal of the American Academy of Religion, 2019)
This article draws on theories of phenomenology, visual anthropology, and embodiment to explore Advaita Vedānta’s sensorial and embodied modes of praxis. It interweaves two threads based on a case study of the Arsha Vidya Gurukulam, an Advaita Vedānta institute in Tamil Nadu, India: (1) an ethnographic analysis of the intersections of textual study, religious praxis, and social-environmental context; and (2) the ways these intersections are grounded in Advaita Vedānta’s source texts. This article focuses on the unique potential of experiential sensory-ethnographic film for revealing these intersections and argues that such films are uniquely capable of providing viewers phenomenological and sensorial insights into individual subjectivities within religious praxis. It further probes how the Advaitin follows a roadmap of metaphysical models, ritual praxis, and receiving a teacher’s textual performance. This process reformulates bodies and identities towards the nondualistic through an interiorization of texts and is essential for remembering and transmitting the tradition.